2023
DOI: 10.1002/smll.202206253
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Based Nanoarchitectures for Sonodynamic Therapy‐Involved Multimodal Treatments

Abstract: Figure 6. A) Schematic mechanism of TKD@RMPB formation and its US stimulus-responsive antitumor behavior. Reproduced with permission. [76] Copyright 2020, Wiley-VCH. B) Schematic illustration for the preparation and the anticancer mechanism of HPT-DOX. Reproduced with permission. [73] Copyright 2020, Wiley-VCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 198 publications
(324 reference statements)
0
8
0
Order By: Relevance
“…Encouraged by the excellent tissue-penetration depth of US and the non-invasiveness during the treatment, SDT shows distinct potential to replace antibiotics treatment and avoid the multiple surgical debridements against osteomyelitis [129] , [130] . Cheng et al reported gold-doped titanate nanotubes conjugated with guanidinium-rich polymer (Au/TNT@PG) for MRSA biofilm elimination by SDT [113] .…”
Section: Applications Of Sdt In Bacterial Infectious Diseasesmentioning
confidence: 99%
“…Encouraged by the excellent tissue-penetration depth of US and the non-invasiveness during the treatment, SDT shows distinct potential to replace antibiotics treatment and avoid the multiple surgical debridements against osteomyelitis [129] , [130] . Cheng et al reported gold-doped titanate nanotubes conjugated with guanidinium-rich polymer (Au/TNT@PG) for MRSA biofilm elimination by SDT [113] .…”
Section: Applications Of Sdt In Bacterial Infectious Diseasesmentioning
confidence: 99%
“…Despite this, it is undeniable that achieving a very successful therapeutic response with monotherapy is typically difficult due to the complex tumor microenvironment. [139][140][141] All known cancer treatments, such as chemotherapy, [142][143][144] chemodynamic therapy, [145][146][147] photodynamic therapy, [148][149][150] photothermal therapy, [151][152][153] and immunotherapy, [154][155][156] have progressed sufficiently independently to significantly complement others. Therefore, many researchers have combined these methods with SDT to improve the overall treatment effect of the disease.…”
Section: Sdt Combined With Other Therapeutic Modalitiesmentioning
confidence: 99%
“…It will greatly reduce the effect of immunotherapy . Besides, the oxygen-dependent treatments, such as photodynamic therapy (PDT) , and sonodynamic therapy, will lose efficacy in the hypoxic environment. Moreover, the oxidative damage to tumor would be reduced, and TME would also cause certain drug resistance .…”
Section: Introductionmentioning
confidence: 99%